REPRESENTASI EMANSIPASI WANITA DALAM FILM “KARTINI" - Ratih Yuswita Sari; Chelsy Yesicha (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Understanding the emancipation of women that exist in the thought of Kartini and misunderstandings do not occur in interpreting the meaning of female emancipation. The discourse of female emancipation in Indonesia could not be separated from the figure of Ajeng Raden Kartini. Since the 19th century, she was remembered as a fighter for women's emancipation in Indonesia. Through a letter addressed on his friends in the Netherlands, She reveals his thoughts about the struggles of women and female emancipation. Kartini's letters are collected in a book published by Mr. j. h. Abendanon Door Duisternis tot under the title Licht in 1911. This research uses qualitative research methods with the study of the analysis of the discourse of Sarah Mills. Sara Mills convey that understanding is divided into two parts, namely the position of the subject – object and the reader or audience. The authors collected data done by processing the documentation, study library and browse the online data. While for the data analysis, the author does categorization and the reduction of data, data and cereal drawdown summary. The results of the research in this is an understanding of female emancipation in the thought of R. A. Kartini's in the movie, She has two wishes. For Kartini his desire as women is to be free and independent. More details are first, as a woman She would like to be given the opportunity of pursuing an education at the school. Kartini's desire that latter is refused the existence of polygamous marriages. Kartini wrote to fight for emancipation of women.The thinking and actions of Kartini as this can not be separated from the background is the son of concubine and comes from the aristocracy. The conclusion of this paper is to struggle for the non educated for women and denial over the marriage of polygamy. In his fight, She uses literature as a tool to achieve this. The experience and background of Kartini as a son of concubine became a compelling reason in the fight for emancipation of women. Not only that, the traditional Javanese too withheld any women participated and motivated Kartini to fight escaping on behalf of women.